2019
DOI: 10.1155/2019/7869318
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Myocardial Ischemia-Reperfusion Injury in Diabetes Mellitus by Inhibiting Endoplasmic Reticulum Stress

Abstract: Objective With the increasing incidence of diabetes mellitus (DM) combined with myocardial ischemia, how to reduce myocardial ischemia-reperfusion injury in DM patients has become a major problem faced by clinicians. We investigated the therapeutic effects of dexmedetomidine (DEX) on myocardial ischemia-reperfusion injury in DM rats and its effect on endoplasmic reticulum stress. Methods SD rats with SPF grade were randomly divided into 6 groups: non-DM rats were divided into the sham operation group (NDM-S gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…In previous studies, DEX exhibited a protective role in the hearts of diabetic mice by interfering with ERS or autophagy, thereby suppressing IRI (6,23); however, the results were partially attributed to the diabetes context. Furthermore, researchers have focused on the study of cells other than cardiomyocytes, such as endothelial cells, under IRI or hypoxia/reoxygenation (H/R) conditions (24,25), and have examined several crucial ERS chaperones, proteins and apoptosis indicators that are produced by organs other than the heart under IRI or H/R conditions (6,(26)(27)(28)(29)(30). These studies have shown that DEX effectively regulates the function of non-cardiomyocytes and interferes with the ERS signaling pathway under these conditions.…”
Section: Dexmedetomidine At a Dose Of 1 µM Attenuates H9c2 Cardiomyocmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies, DEX exhibited a protective role in the hearts of diabetic mice by interfering with ERS or autophagy, thereby suppressing IRI (6,23); however, the results were partially attributed to the diabetes context. Furthermore, researchers have focused on the study of cells other than cardiomyocytes, such as endothelial cells, under IRI or hypoxia/reoxygenation (H/R) conditions (24,25), and have examined several crucial ERS chaperones, proteins and apoptosis indicators that are produced by organs other than the heart under IRI or H/R conditions (6,(26)(27)(28)(29)(30). These studies have shown that DEX effectively regulates the function of non-cardiomyocytes and interferes with the ERS signaling pathway under these conditions.…”
Section: Dexmedetomidine At a Dose Of 1 µM Attenuates H9c2 Cardiomyocmentioning
confidence: 85%
“…Myocardial ischemia-reperfusion injury (MIRI), which usually occurs in clinical settings, leads to severe outcomes for patients if no effective strategies are applied to inhibit the downstream apoptotic cascades. However, numerous animal studies that have revealed various protective mechanisms have also confirmed the efficacy of cardioprotection in overcoming MIRI (1)(2)(3)(4)(5)(6). However, the results achieved in the clinical application of these strategies have not been consistent with those achieved in experimental research (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Judging from existing studies, DEX performs a protective role in inhibiting IRI in the heart of diabetic mice by interfering with ERS or autophagy; 6,15 however, these results were partly attributed to the diabetes context. Furthermore, researchers have focused on studying other non-cardiac cells, such as endothelial cells, under IRI or H/R conditions 16,17 and examining several crucial ERS chaperones, proteins and apoptosis indicators produced by organs other than the heart under IRI or H/R conditions, 6,[18][19][20][21][22] finding that DEX can effectively regulate the function of non-cardiac cells and interfere in the endoplasmic reticulum stress signalling pathway under certain circumstances. Few studies have explored the function of DEX in H9c2 cardiomyocytes under H/R conditions; 23,24 however, the exact regulatory effect of DEX on ERS remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Fortunately, numerous animal studies evaluating diverse protective mechanisms have confirmed the efficacy of cardioprotection in ameliorating MIRI. [1][2][3][4][5][6] The actual clinical application of some of these strategies, however, does not match the animal study applications, and it is difficult to predict the consequences in clinical practice from those seen in experimental research. [7][8][9] In this context, the unclear mechanism underlying the development of apoptotic pathways or involving key molecules in MIRI might significantly matter, especially for cell death and even associated signalling pathways during ischaemia-reperfusion, such as ERS-related apoptosis or signalling pathways; a noteworthy report by Davidson in 2019 shared the opinion that multitarget strategies must be adopted to reduce MIRI if appropriate because single approaches have a limited capacity to overcome complicated MIRI situations.…”
Section: Introductionmentioning
confidence: 99%
“…But excessive ER stress induces apoptosis 7 . Previous studies revealed that ER stress–initiated apoptosis plays a very important role in MI/R injury 8 , 9 . Therefore, ER stress, as a potential target for the treatment of I/R-induced myocardial injury, has been an area of extensive research.…”
Section: Introductionmentioning
confidence: 99%